Clinicopathological correlation in the diagnosis of granulomatous cutaneous disorders: a retrospective study - Nijhawan, Manisha; Yadav, Divya; Nijhawan, Shivi; Shaktawat, Damini (International Journal of Research in Dermatology, 2021)
Background: To ascertain the various cutaneous granulomatous disorders and clinicopathological concordance in skin biopsies. Methods: The study included the patients with skin biopsy showing granulomatous infiltrate in a tertiary care center. The cases were categorized according to level of concordance into consistent, corroborative and inconsistent based on the concurrence between clinical and histological diagnosis. Results: Of the total 155 granulomatous disorder, 75.48% showed clinicopathological concordance, 19.35% showed corroborative diagnosis while 5.16% were inconsistent. The maximum number of biopsies performed were in the group of young adult (19-49 years, 57.41%). The most common type of granuloma found was of tuberculoid type and disorders were Hansen’s disease, fungal infection and cutaneous tuberculosis. Conclusions: Our study showed that the coordination of dermatologist and pathologist plays a pivotal role in making accurate diagnosis of granulomatous cutaneous dermatoses.